The Six Sigma approach in performance management to improve safety culture at work. (15th September 2008) - Lok, Peter; Rhodes, Jo; Diamond, Abe; Bhatia, Nitin
This case study uses the Six Sigma process framework in performance management to explore and decrease the injury rate of an international waste disposal firm. The results indicate that an employee-management consensus approach to continuous improvement in safety management in the workplace is essential. The evidence from this case suggests that the Define, Measure, Analyse, Improve and Control (DMAIC) Six Sigma process and an analysis tool such as the fishbone diagram can be easily adopted as measurements and reduce the injury rate in the workplace. Furthermore, the case shows that management commitment and employee ownership of the Six Sigma programme is the key to continuous improvement and the development of a safety culture and a learning organisation.